Adsorption Kinetic and Thermodynamic Study of Congo Red Dye on Synthetic Zeolite and Modified Synthetic Zeolite - M. Abbas, Ahmed; I. Mohammed, Yousif; A. Himdan, Taki (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Linde Type-A (LTA) zeolite was modified by adding  lead sulfide into cavities of zeolite. The zeolite and zeolite â€“pbs  were characterized by FTIR, XRD, AFM and SEM. The adsorption of congo red (CR)  dye  from aqueous solution by zeolite and zeolite â€“ pbs were studied. Different parameters like contact time, temperature and concentration of (CR) dye were investigated. The results show that at contact time of 45, 30 min for maximum adsorption of (CR) dye onto zeolite and zeolite -pbs respectively were observed. The kinetic data was analyzed using pseudo-first-order and pseudo-second-order kinetic models. The adsorption kinetics of (CR) dye  were fitted well with the pseudo-second-order kinetic model for both adsorbents. Experimental equilibrium data onto adsorption of C-R dye on zeolite and zeolite â€“pbs were analyzed by the Langmuir, Freundlich and temkin isotherm models .The calculated thermodynamic parameters, namely Î”GÎ¿, Î”HÎ¿, and Î”SÎ¿ for zeolite showed that adsorption of C-R dye onto zeolite was spontaneous , endothermic and increase in the randomness and for zeolite â€“pbs showed that adsorption of C-R dye onto zeolite -pbs was spontaneous and ,exothermic and decreasing randomness  under examined conditions ,The results of analysis errors and R2 values shows that the best fit was achieved with the  Langmuir isotherm equation and were followed order:-  ( Big R2) langmuir > temkin > freundlich( small R2) ( small error) Langmuir < temkin < freundlich( big error)